2015
DOI: 10.1167/15.6.15
|View full text |Cite
|
Sign up to set email alerts
|

Saccadic inhibition and the remote distractor effect: One mechanism or two?

Abstract: It has been hotly debated whether a single mechanism underlies two established and highly robust oculomotor phenomena thought to index the competitive nature of eye movement plans: the remote distractor effect and saccadic inhibition (SI). It has been suggested that a transient mechanism underlying SI would not be able to account for the shift in the saccade latency distribution produced by early distractors (e.g., those appearing 60 ms before target onset) without additional assumptions or a more sustained so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 15 publications
(35 reference statements)
0
13
0
Order By: Relevance
“…However, our data cannot reveal if onsets increased or decreased saccade latencies, especially since we lack an informative control condition. Sudden distractor onsets can also give rise to saccadic inhibition that is characterized by a dip in the latency distribution around 70-100 ms after distractor onset (Bompas, Campbell, & Sumner, 2020;Bompas & Sumner, 2015;Buonocore & McIntosh, 2008;Edelman & Xu, 2009;Reingold & Stampe, 1999. Saccadic inhibition is thought to arise from competing activation in saccade planning areas like the superior collicus (SC; Dorris, Olivier, & Munoz, 2007;Meeter, Van der Stigchel, & Theeuwes, 2010;White et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…However, our data cannot reveal if onsets increased or decreased saccade latencies, especially since we lack an informative control condition. Sudden distractor onsets can also give rise to saccadic inhibition that is characterized by a dip in the latency distribution around 70-100 ms after distractor onset (Bompas, Campbell, & Sumner, 2020;Bompas & Sumner, 2015;Buonocore & McIntosh, 2008;Edelman & Xu, 2009;Reingold & Stampe, 1999. Saccadic inhibition is thought to arise from competing activation in saccade planning areas like the superior collicus (SC; Dorris, Olivier, & Munoz, 2007;Meeter, Van der Stigchel, & Theeuwes, 2010;White et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, a large peripheral distractor presented shortly after the target strongly reduces the probability of triggering a saccade around 100 ms after the distractor appearance, a phenomenon called saccadic inhibition (SI) which results in a dip in the saccade latency distributions [43]. It has been proposed that these are one and the same phenomenon, where SI would be the underlying mechanism of the RDE [44,45]. In our experiment, when adding a full screen visual flash shortly after the target onset we create the condition where SI takes place.…”
Section: Discussionmentioning
confidence: 99%
“…Dorris, Olivier, and Munoz (2007) subsequently confirmed that preparatory activity for an expected saccade target is decreased transiently by the onset of a distractor elsewhere in the visual field (nearby distractors can conversely facilitate build-up activity). Recently, a physiologically inspired model, incorporating long-range inhibition and local facilitation, has been found to simulate empirical patterns of saccadic inhibition with impressive accuracy (Bompas & Sumner, 2011, 2015.…”
Section: Discussionmentioning
confidence: 99%